Monitoring and evaluation of programmes to prevent mother to child transmission of HIV in Africa. Issue 7604 (31st May 2007) - Reithinger, Richard; Megazzini, Karen; Durako, Stephen J; Harris, D Robert; Vermund, Sten H
Abstract : Many countries are expanding the coverage of programmes to prevent mother to child transmission of HIV. Although the need is unquestionable, Richard Reithinger and colleagues are concerned that without true measures of effectiveness we may not be making the best use of resources